SOMATIC EMBRYOGENESIS FROM MERISTEM EXPLANTS OF GINGER - Otih Rostiana; Sitti Fatimah Syahid (SEAMEO BIOTROP, 2008)
The use of planting materials from in vitro culture, especially derived from somatic embryos has some advantages such asÂ genetically stable and pathogen-free. Meristem culture of ginger through somatic embryogenesis could be a potential method for producing pathogen-free planting materials. Somatic embryogenesis on ginger was performed to obtain vigorous plantlets having the same rhizome size as the mother plant. Callus was induced from meristem tissue of inner bud of Indonesian ginger rhizome Var. Cimanggu-1 and consecutively subcultured into certain media at each steps of experiments. The vigorous embryogenic calli were observedÂ on MS medium containing 100 mgl-1 glutamine and 2% sucrose with addition of 1.0 mgl-1 2,4-D + 3.0 mgl-1 BA. The highest number of somatic embryos (about 82.0.g-1 friable calli) was achieved on that medium, 4 weeks after culturing. Furthermore, the optimum growth of embryogenic calli containing somatic embryo was obtained on MS medium enriched with 6% sucrose. The highest number of mature somatic embryos (57.2 embryos) was achieved on MS medium, 18 days after incubation. The regeneration potency of somatic embryos obtained from ginger meristem was 51.20%.g-1 friable callus. The valuable result of this study was the achievement of normal rhizome size of regenerated plantlets, instead of micro rhizome.